TRANSFORMASI ISLAM INDONESIA DALAM TREND GLOBAL: MENCARI PENJELASAN “MODERASI BERAGAMA” DI RUANG PUBLIK - Ahmad Suaedy (LIPI Press, 2022)
Religious Moderation (MB) is a government program aimed at overcoming certain problems that are currently taking place in Indonesia but for the long-term goal of building the character of the Indonesian nation. The challenges are mainly what the government perceives as radicalism, religious violence and left and right extremism which are considered to threaten the sustainability of the nation and the unity of Indonesia. However, MB is unique because it explicitly places religion as a key in it, unlike other programs. Therefore, it is important to look at this MB not only at the changes in the Jokowi administration era but also changes in Indonesia in general and even in the global context. In the recent global shift, it is inevitable that religious factors will emerge in public space and policies, and Indonesia is no exception. By some academics this phenomenon is called post secular and public religion. In the West, it is caused by the flood of immigrants who come to developed countries with different cultures, traditions and religions but because of the number and cultural strength, they push for change in these societies. In Indonesia, demographic changes also occur due to class social mobility that affects new shifts and balances as well as the entry of religion into the public and government spheres. This paper will place the MB public policy which is currently being intensively carried out by the Indonesian government in the shift map. Is it a regression of democracy or a form of democracy typical of Indonesia: a country that has strong spiritual and religious historical characteristics and a thick plurality of people. In this case, in Indonesia, the public sphere of democracy cannot isolate religion in the private sphere, when it comes to enforcing democracy which requires broad civil society participation.